Safety and Design Aspects of Powered Toothbrush-A Narrative Review - Clarence Ng; James Kit Hon Tsoi; Edward C. M. Lo; and Jukka P. Matinlinna (MDPI AG, 2020)
The powered toothbrush has become a modern dental tool that is available in the supermarket. Indeed, the design of the powered toothbrush, e.g., mechanical and electrical, would affect not only the efficacy but also the safety of the products. This narrative review attempted to view the powered toothbrush from design, safety, and application points with respect to tufts, filaments, handles, mechanics, motions, and materials interactions from various available sources. Different brands and models of powered toothbrushes have their own designs that might affect the clinical outcome. The rotational design was advocated to be clinically more effective than the manual one, some modern models might be designed with vibrational or oscillation (or mixed) tufts head that might be useful in patients with specific needs, such as having xerostomia or for the elderly. To conclude, tuft retention design is important in the powered toothbrush as it contributes significantly to safety as the fallen off tufts, filaments and metal parts might cause injury. Tests revealing the retention force of brush head plates and brush head bristles will be significant references for consumers to determine which design of powered toothbrushes is relatively safer.